Analysis of The Utilization and Implementation of Cloud Computing Infrastructure Services on The Azure Microsoft Platform - Nur Alamsyah; Nur Imam Febrianto (Institute of Computer Science (IOCS), 2021)
This final project discusses cloud computing infrastructure services, where cloud computing is the evolution of various computing technologies that have existed since the early 1960s. This final project will discuss cloud computing infrastructure services on the Microsoft Azure platform. Microsoft Azure is a hyperscale cloud computing platform that has many services, one of which is infrastructure as a services. DNS server implementation will be carried out to test the functionality of the Microsoft Azure service. Analysis of the performance of both the processor compute, memory bandwidth, network throughput and storage media performance will be tested and compared with the on-premise system. The applications used for performance testing are LINPACK, STREAM, iperf and also fio. The on-premise system being compared is a virtualization-based system using the VMware vSphere platform and hardware specifications that are made closer to the server specifications on Microsoft Azure. Costs incurred for operations and investment as total cost of ownership of an on-premise infrastructure system with Microsoft Azure infrastructure services will be compared, including the costs required to implement a server on an on-premise system with implementation on Microsoft Azure.